Relationship between expected progeny differences (EPD) and performance of Angus and Simmental bulls in central bull tests - Simms, D.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The performance of bulls (n = 656 for Angus and n = 1343 for Simmental) at the Beloit and Potwin bulls tests from 1989 to 1992 were compared to their expected progeny differences (EPDs). In general, correlations between on-test ADG and weaning and yearling EPD were low for both breeds. However, the correlations between actual yearling weight and yearling EPD was moderate for Angus. Differences in actual yearling weight were 2.80 and 1.71 pounds (for Angus and Simmental, respectively) for each pound of difference in yearling weight EPD, which is close to the 2.0 pound difference expected. Thus, although the relationship between EPDs and average daily gain on test was not strong, EPDs did a good job of predicting differences in weight at a standardized age.
Keywords: Beef; Bull tests; Expected progeny differences